The efficacy of a transdiagnostic group cognitive behavioral intervention for Chinese elderly with emotional disorders: A one-year follow-up randomized clinical trial - Yan, Zijun; Meng, Fanqiang; He, Meiling; Li, Zhanjiang (Frontiers in psychiatry, 2022)
With the global aging, geriatric emotional disorders have received more and more attention. Psychotherapy is an effective approach for alleviating the symptoms associated with emotional disorder, but the number of experienced therapists is low. Studies should be conducted to explore a low-cost and efficient treatment method. Previous findings indicate that transdiagnostic cognitive behavior therapy is an effective approach for treatment of emotional disorders. Group therapy is appropriate for the elderly as they are characterized by high levels of loneliness. In this study, we compared and explored the effects of a transdiagnostic group cognitive behavioral intervention (TD-GCBT), a transdiagnostic individual cognitive behavioral intervention (TD-CBT), and treatment as usual (TAU) on treatment of emotional disorders among the elderly. A total of 120 elderly patients diagnosed with emotional disorders were randomly assigned to the TD-GCBT group (40), TD-CBT group (40), and TAU group (40). Changes in symptoms were assessed using HAMD, PHQ-9, HAMA, and GAD-7 scales at baseline, post-treatment (three months), six-month and twelve-months follow-up. The efficacies of the three intervention strategies were compared using linear mixed-effects models. and simple effect analyses were conducted to determine the differences among the three groups. The HAMD, PHQ-9, HAMA, and GAD-7 scores revealed a significant effect from baseline to 12 months for time ( < 0.001), group ( < 0.001) and time × group interaction ( < 0.001) in TD-GCBT group compared with the TD-CBT group and TAU group. The effect of TD-GCBT (HAMD: Cohen's (3th month, 6th month, 12th month) = 2.69, 3.98, 4.51; HAMA: Cohen's = 2.84, 4.13, 5.20) and TD-CBT (HAMD: Cohen's = 2.55, 2.87, 2.63; HAMA: Cohen's = 2.43, 2.83, 2.78) group was better relative to that of the TAU group (HAMD: Cohen's = 0.41, 1.13, 1.46; HAMA: Cohen's = 0.64, 1.22, 1.57) ( < 0.001). The scores of the TD-GCBT group showed the most significant decrease compared with the other two groups. The findings indicate that TD-GCBT method is effective for treatment of emotional disorders among the elderly. TD-GCBT is effective for alleviating depression and anxiety symptoms up to at least nine months after treatment. The results indicate that TD-GCBT is a cost-effective and resource-effective strategy and can be used an alternative therapy for treatment of mental disorders. [https://www.chictr.org.cn], identifier [ChiCTR1900021806].